Childhood trauma is associated with altered white matter microstructural organization in schizophrenia. (April 2023) - Dauvermann, Maria R.; Costello, Laura; Tronchin, Giulia; Holleran, Laurena; Mothersill, David; Rokita, Karolina I.; Kane, Ruán; Hallahan, Brian; Corvin, Aiden; Morris, Derek; McKernan, Declan P.; Kelly, John; et al.
Highlights: Individuals with schizophrenia showed fractional anisotropy (FA) reductions compared to controls. High trauma levels were related to FA reductions compared to those with none/low levels. No interaction between diagnosis and high levels of childhood trauma was found. The effects of trauma severity on white matter organization may be independent of schizophrenia. Abstract: It has been reported that childhood trauma (CT) is associated with reductions in fractional anisotropy (FA) in individuals with schizophrenia (SZ). Here, we hypothesized that SZ with high levels of CT will show the greatest reductions in FA in frontolimbic and frontoparietal regions compared to healthy controls (HC) with high trauma levels and participants with no/low levels of CT. Thirty-seven SZ and 129 HC with CT experience were dichotomized into groups of 'none/low' or 'high' levels. Participants underwent diffusion-weighted MRI, and Tract-based spatial statistics were employed to assess the main effect of diagnosis, main effect of CT severity irrespective of diagnosis, and interaction between diagnosis and CT severity. SZ showed FA reductions in the corpus callosum and corona radiata compared to HC. Irrespective of a diagnosis, high CT levels ( n  = 48) were related to FA reductions in frontolimbic and frontoparietal regions compared to those with none/low levels of CT ( n  = 118). However, no significant interaction between diagnosis and high levels of CT was found ( n  = 13). Across all participants, we observed effects of CT on late developing frontolimbic and frontoparietal regions, suggesting that the effects of CT severity on white matter organization may be independent of schizophrenia.